Studi Prestasi Taekwondo Pada Nomor Kyorugi Dan Pada Nomor Poomse Di Kota Bengkulu - rizky govinda; dian pujianto; yarmani yarmani (Universitas Bengkulu, 2020)
This Study aims to determine The Achievement Of Taekowondo On Kyorugi Numbers And On Poomse Numbers In Bengkulu City. This type research is descriptive qualitative. Subjects in this study were athletes, club administrators (coach), coaches with total 36 people. Data collection teghnigues used were surveys (questionnaires), and documentation. The instrument used was a closed questionnaire, the data analysis technique used is percentage. The result of this study were taken from the athelet questionnaire, club managers (coaches) with a total of 36 people, then the questionnaire result were obtained with a percentage of 82,7% of the criteria of strongly disagree, 89,9% of the trainers in the sufficient category, and the management obtained result wit percentage 90,2%. With enough kategory , so it can be conclude that Achievement Study Of Taekwondo Atheles In Kyorugi Numbers And Poomse Number In Bengkulu City has sufficient categories with an average score of 157,8 ( 87,62%).